Previsão de tensão em sistemas de distribuição considerando as possibilidades das redes inteligentes - Garcia, Enoque Dutra (2012)
With the deployment of Smart Grids, the voltage quality has a new focus, and the ANEEL (National Agency of Electric Energy), Brazilian regulator organ, is able to improve its supervision activity. The electric energy customer has access to the value of voltage in real time and the utility needs to identify alternatives to attend the rigor of the regulatory acts and the intense expectative of its customers. Nowadays, in the conventional networks, the voltage setting is performed from the reference voltage set point of itself or of center of load. In the scenario of Smart Grids, beyond these values, it is also possible to use the online measures at any point of the feeder. In this new scenario it is possible to indentify alternatives related to advances in distribution networks power quality, in this way, the present work shows a methodology to be used as tools of operational support in the control of voltage profile in primary networks. Through application of computational intelligent techniques it is suggested a system of steady state voltage prediction for the monitored points along the feeder. The loading system and meteorological informations are used for the method application. From the result obtained for the very-short time forecasting, it is introduced the concept of Smart Grids, which considers proactive actions to optimize the process of maintenance of voltage level.